A turning point in a student’s Life in the prison camp of Gaza / occupied Palestine - Ismael, Abu-Jarad

(untitled)
The Prison Camp of Gaza in Occupied Palestine is a 5 by 25 mile strip facing the Mediterranean from the west, the borders with Egypt from the south, and the territories of what was called State of Israel back in 1948 from the east and north. I call The Gaza Strip a prison camp because it has been under an Israeli blockade since 2006 where people cannot go out or in Gaza. More than 350 patients who were in bad need of medical treatment died because they could not go to Egypt to receive the necessary medical treatment they needed. Those patients are perceived as martyrs by the community in Gaza.